Environmental Discrimination and the Charter’s Equality Guarantee: The Case of Drinking Water for First Nations Living on Reserves - Chalifour, Nathalie (Revue générale de droit)

(untitled) (Éditions Wilson & Lafleur, inc., 2013)
Many First Nations communities living on reserves in Canada do not have consistent access to one of the most essential requirements for life—clean and safe drinking water. This article analyses the Charter’s equality guarantee to determine whether it offers a remedy. The analysis shows that the experience of First Nations communities living on reserve without access to clean water is discriminatory within the meaning of s 15 of the Charter, and that this discrimination would not be saved by s 1. The most significant hurdle to a s 15 claim is the fact that there is no single law which categorically excludes First Nations reserve communities from its protection. While the courts have not considered a case with similar facts, the article argues that the Charter’s equality protections extend to the full range of government action (and inaction) regardless of whether the action stems from one law, regulation or policy, or a set of laws that, acting together, creates discrimination. An interpretation that would limit s 15 protections based on a narrow, formalistic interpretation of the word “law” in section 15 would not only run counter to the interpretations of the section in recent decisions, but more importantly would run afoul of the Charter’s purpose of promoting substantive equality.